(untitled) (Confluenţe Bibliologice, 2012)
On 28-29 November 2012, Library Association of the Republic of Moldova (LARM) organized the VII-th Congress of Librarians in Moldova entitled „Libraries Now! Inspiring, Surprising, Empowering!“ Scientiﬁc Library of the State University „Alecu Russo“ of Balti was represented by 5 delegates: Elena Harconița, Lina Mihaluța, Valentina Topalo, Stratan Elena, Silvia Ciobanu. The Congress elected a new President and approved the resolution theme: „The Library – Investment in the Future”.